2008
DOI: 10.1007/s12022-008-9035-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Dysadherin in Papillary Thyroid Carcinoma and Microcarcinoma: Correlation with E-cadherin

Abstract: Dysadherin is a novel glycoprotein, with an anti-cell-cell adhesion function. The aim of the present study was to examine the expression of dysadherin in thyroid papillary microcarcinoma (PMC), to associate it with the expression of E-cadherin and to investigate whether there are differences with papillary carcinoma (PC). A statistically significant difference in dysadherin and E-cadherin expression between PC and PMC and a negative correlation between E-cadherin and dysadherin expression regardless of tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
2
13
2
Order By: Relevance
“…These results are in accordance with those of previous studies investigating E-cadherin expression in PTCs of all stages (23)(24)(25)(26)(27). Certain studies demonstrated a correlation between the loss of E-cadherin expression and disease progression or poorer prognosis in PTC (27,29); however, the results of the present study did not verify the clinical significance of E-cadherin expression in PTMC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with those of previous studies investigating E-cadherin expression in PTCs of all stages (23)(24)(25)(26)(27). Certain studies demonstrated a correlation between the loss of E-cadherin expression and disease progression or poorer prognosis in PTC (27,29); however, the results of the present study did not verify the clinical significance of E-cadherin expression in PTMC.…”
Section: Discussionsupporting
confidence: 93%
“…E-cadherin is a well-known cellular adhesion molecule in epithelial cells and is known to be lost during the process of EMT. E-cadherin expression is commonly observed in differentiated thyroid cancer (23)(24)(25)(26)(27) and loss of its expression was reported to be an independent prognostic factor for these tumors (27).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Naito et al (2001) found that E-CAD expression was preserved significantly less often in papillary cancer with lymph node metastasis than in node-negative cases, but E-CAD expression did not correlate significantly with other clinical factors including tumor diameter, extracapsular tumor extension or histological differentiation [12]. These and our results are thus in contrast to those reported by Brabant, von Wasilewski, Scheumman, Walgenbach and Batistatou [8][9][10][11]31]. Brabant et al (1993) observed lower or undetectable E-CAD immunoreactivity in tumors presenting lymph node metastases, distant metastases or local recurrence [8].…”
Section: Discussioncontrasting
confidence: 97%
“…Scheumman et al (1995) and Walgenbach et al (1998) reported that reduced (below 30% in the study by Scheumman and < 20% -in Walgenbach's study) or negative E-CAD expression was associated with advanced T categories of the primary tumors and higher rates of lymph node involvement and distant metastasis [9,10]. Batistatou et al (2008) found that the reduction of E-CAD expression in papillary microcancers was smaller than in other papillary cancers [31]. Our data did not confirm those observations.…”
Section: Discussioncontrasting
confidence: 61%
“…In many tumor tissues, the protein level of FXYD5 inversely correlates with the level of E-cadherin (Batistatou et al, 2008;Maehata et al, 2011;Mitselou et al, 2010;Ono et al, 2010;Shimada et al, 2004); however, whether this is a result of FXYD5-induced downregulation of E-cadherin is unknown. Overexpression of FXYD5 reduced the levels of E-cadherin in particular cell lines (Ino et al, 2002), but had no effect in others (Lubarski et al, 2011).…”
Section: Discussionmentioning
confidence: 99%